Coagulation-flocculation mechanism of hylocereus undatus foliage in wastewater treatment: article - Ramlee, Aina Afiqah; Md Som, Ayub; Puasa, Siti Wahidah (2019)
The floc particles formed during perikinetic and orthokinetic flocculation from molecular point of view was investigated and the effect of pH on zeta potential during coagulation flocculation process of wastewater using hylocereus undatus foliage was determined. Dragon fruit foliage is known to carry the characteristics of a natural coagulant. However, no previous study is carried out to unlock the fundamental theory behind the coagulation – flocculation mechanism in the application of hylocereus undatus foliage as a plant-based coagulant. Hence, this study was conducted without the addition of any synthetic coagulants and zeta potential was used as parameter in observing magnitude charges between particles. Jar test experiments were done using pharmaceutical wastewater and hylocereus undatus foliage as coagulant with different range of pH and analytical analysis was performed. Through FTIR spectroscopy, it was found that the functional groups of aliphatic primary amines, secondary amines and carboxylic acids, which are among protein-specific groups, were accountable for good coagulation activity. The zeta potential of dragon fruit foliage was found to be +0.433 mV indicating it to be a cationic coagulant. The mechanism of coagulation process is suggested to be charge neutralization and absorption since the zeta potential of wastewater was initially -7.72 mV but decreases to -2.65 mV at optimum pH 3. Moreover, as the pH increases the zeta potential becomes more negative due to the dominant adsorption of OH- in alkaline pH conditions